First assessment of flux rates of jellyfish carcasses (jelly-falls) to the benthos reveals the importance of gelatinous material for biological C-cycling in jellyfish-dominated ecosystems - Sweetman, Andrew K.; Chapman, Annelise (Frontiers in Marine Science, 2015)
There is accumulating evidence that jellyfish contribute significantly to biological carbon cycling and that their carcasses can have controversial effects on seafloor ecosystems. Moreover, changes in the thermal properties of the ocean, ocean chemistry and direct anthropogenic effects can seriously modify jellyfish populations in surface waters and potentially alter the importance of jellyfish in the biological pump relative to other forms of detritus. However, no studies have ever quantified the flux rate of jellyfish carcasses (jelly-falls) to the seafloor, or quantified how jelly-fall C and N fluxes compare to phytodetrital fluxes. In this study, we documented the seafloor abundance of jelly-falls over a 1-year period in the jellyfish-dominated Lurefjord, western Norway. A total of 9 jelly-falls were documented from 768 seafloor images over the course of the study, equivalent to 0-13.4 mg C m-2 and 0-2.1 mg N m-2 of jellyfish material being deposited in the deep fjord basin. Assuming that jellyfish removal rates and phytodetrital flux rates from nearby fjord environments are similar to Lurefjorden, we estimate that the jellyfish C and N fluxes to the seafloor were 0-72.8 mg C m-2 d-1 and 0-11.2 mg N m-2 d-1 at the time of sampling. In addition, we estimate that the maximum jellyfish carcass flux rates were equivalent to 96 and 160% of the phytodetrital C and N flux that would arrive at the seafloor where the jelly-falls were recorded. These results imply that jelly-falls most likely contribute significantly to detrital C and N fluxes in at least one jellyfish-dominated environment, despite often being recorded in low abundances. If more fjord environments become jellyfish hotspots as a result of water column darkening, the contribution of jellyfish C and N in the biological pump will potentially increase, necessitating the conceptual inclusion of a jelly-pump in future fjord biogeochemical cycling studies.